Estudo do complexo mer-[RuCl3(dppb)(VPy)]: síntese, caracterização e potenciais aplicações - Sandrino, Bianca (2010)
The synthesis of biphosphine complex, specifically containing the unit “[RuCln(dppb)]” (dppb = 1,4-bis(diphenylphosphino) butane), has attracted considerable interest due to applications in catalysis for hydrogenation of organic compounds and more recently in biological activities and modified electrodes due to its stability and promising redox property. Within this perspective, in this work the complex mer-[RuCl3(dppb)(VPy)] (VPy = 4-vinylpyridine), RuVPy was synthesized from the replacement of the aqua ligand of the complex mer-[RuCl3(dppb)H2O] by ligand 4-vinylpyridine in the ratio 1:1.1 (complex / ligand). Spectroscopic results indicated that the incorporation of the ligands dppb and VPy yielded bands at 435, 516, 1002, 1087, 1433 and 1484 cm-1, 262, 390, 450, 530 nm coincident with spectra of the serie complex mer-[RuCl3(dppb)(L)] (N-heterocyclic). Values of g tensor (g1 = 2.40, g2 = 2.00 and g3 = 1.69) confirmed the meridional arrangement of chloride ligands around the octahedral complex geometry. An interesting voltammetric profile was observed for RuVPy solution due to the presence of three peaks with oxidation potential values of 0.07, 0.42 and 0.54 V (vs. Ag/AgCl) that emerged after the reduction of core metallic -0.07 V, attributed to redox processes of complexes [Ru2Cl5(dppb)2], [RuCl2(dppb)(4-VPy)2] and [Ru2Cl4(dppb)2(4-VPy)] formed in solution. Immobilization the RuVPy on different surfaces (LB films, casted film, dip-coated film and carbon paste) revealed only one electrochemical process around 0.55 V (vs. Ag/AgCl) assigned to the redox couple RuII/RuIII. Also, was found that the nature of the nanostructured LB films of RuVpy compared to thick films without structural organization due to the higher peak current compared to the films casted films, dip-coated electrode and carbon paste. The versatility of the RuVpy complex was demonstrated by the conversion of 82.5% of cyclohexene in cyclohexane in the hydrogenation catalysis and the conversion of 91% of cyclooctene in epoxide in the oxidation catalysis. Finally, preliminary catalytic tests showed a lower conversion (67%) in the oxidation of cyclooctene when RuVPy is immobilized on silica.